2014
DOI: 10.1192/apt.20.6.368
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant treatment for postnatal depression

Abstract: pub2 (see www.thecochranelibrary. com for information). Cochrane Reviews are regularly updated as new evidence emerges and in response to feedback, and the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the review. We thank the Cochrane Review Group for their support in publishing these reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 0 publications
0
35
0
4
Order By: Relevance
“…69 Successful treatment of maternal depression may reduce these risks. 70 Breastfeeding is not contraindicated during treatment with an antidepressant medication. Concerns about breastfeeding during medication treatment include short-term adverse reactions and longer-term neurodevelopmental effects.…”
Section: How Is Depression Treated During the Postpartum Period?mentioning
confidence: 99%
See 1 more Smart Citation
“…69 Successful treatment of maternal depression may reduce these risks. 70 Breastfeeding is not contraindicated during treatment with an antidepressant medication. Concerns about breastfeeding during medication treatment include short-term adverse reactions and longer-term neurodevelopmental effects.…”
Section: How Is Depression Treated During the Postpartum Period?mentioning
confidence: 99%
“…Second-line treatments include citalopram, escitalopram, and sertraline, which have data for effectiveness during the postpartum period, minimize risk during lactation, and pose the least known risk during the childbearing years. 70 Structured exercise and depression-specific acupuncture are complementary and alternative treatments that have some evidence in the postpartum period. [71][72][73] An increasing body of evidence also supports the use of therapist-assisted Internet-based behavioural activation and CBT, whereas the effectiveness of unsupported Internet-based psychotherapeutic interventions has not been established.…”
Section: How Is Depression Treated During the Postpartum Period?mentioning
confidence: 99%
“…Antidepressant medication is commonly used as a firstline treatment for postnatal depression, and selective serotonin reuptake inhibitors are likely to be effective 16 ; however, potential medication adverse effects are worrisome to both mothers and clinicians. 17 Transmission through breast milk is a concern.…”
Section: Management Of Postnatal Depressionmentioning
confidence: 99%
“…In addition, it has not been confirmed that adding SSRI to the therapy significantly improved its effectiveness [46,47].…”
Section: Discussionmentioning
confidence: 99%